Serum paraoxonase 1 activity in women with metabolic syndrome - (:unkn) unknown (POLSKIE TOWARZYSTOWO KARDIOLOGICZNE, 2010)
Background: Metabolic syndrome (MetS) is a leading risk factor for coronary artery disease (CAD) in women. Reduced paraoxonase 1 (PON1) activity may play a role in the pathogenesis of atherosclerosis through increased susceptibility to lipid peroxidation in patients with MetS. Aim: To examine whether there is a relationship between serum PON1 activity and MetS in women. Method: The study group consisted of 54 women with MetS. The NCEP ATP III guidelines were used to define MetS. The control group consisted of 65 women without MetS and CAD. All patients from the MetS group underwent coronary angiography. Results: The PON1 activity and salt-stimulated PON1 activity were not significantly altered in women with MetS when compared to controls (p = 0.902, p = 0.877, respectively). There was no significant difference in PON1 activity (p = 0.159), and salt-stimulated PON1 activity (p = 0.139) between diabetics and non-diabetics. In the MetS group, patients with CAD (n = 16) had significantly reduced PON1 activity and salt-stimulated PON1 activity compared to MetS patients without CAD (p = 0.008 and p = 0.004, respectively). Conclusions: Serum PON1 activity is significantly reduced in women with CAD and MetS. MetS per se does not alter serum PON1 activities.
Keywords: paraoxonase activity; metabolic syndrome; coronary artery disease; CORONARY-ARTERY-DISEASE; LOW-DENSITY-LIPOPROTEIN; HYDROLYTIC ACTIVITY; DIABETES-MELLITUS; OXIDATIVE STRESS; PREVALENCE; POLYMORPHISM; ASSOCIATION; PHENOTYPE; IMPACT